Social contagion influenced by active-passive psychology of college students - Ye, Jianmeng; Chen, Yi (Frontiers in Physics, 2022)
2 ABSTRACT Educational behavioral psychology refers to the fact that college students within campus networks 34 have various psychological cognition toward novel information and behavior. This is hardly 5 ever taken into account or theoretically examined in weighted network research. According to 6 psychological traits and a student’s willingness to adopt fresh behaviors, we categorize students’ 7 behaviors into active and passive. On this basis, a threshold models is established for the behavior 8 of active and passive students in weighted networks, and the influence behavioral psychology 9 on information propagation is discussed. In order to qualitatively investigate the information 10 propagation mechanism, a partition theory based on edge-weight and behavioral psychology 11 is developed. Active students encourage the acceptance of new behaviors and the spread of 12 information, according to theoretical study and simulation results. However, the phase transition 13 intersected was more significant. When the percentage of enrolled pupils is high, a continuous 14 phase transition is present in the growth pattern of the final adoption size. In contrast, as the 15 proportion of active students declines, the increasing pattern alterss to discontinuous phase 16 transition. In addition, weight distribution heterogeneity facilitates the dissemination of information 17 and does not alter phase transition pattern. Finally, the theoretical analysis is in good agreement 18 with the simulation results.